Reproductive preferences during middle childhood and early adolescence in Guatemala. Issue 6 (3rd June 2019) - Maupin, Jonathan; Hackman, Joseph
Abstract: Reproductive preferences and the spread of low fertility norms occupy a key position in debates regarding the causal mechanisms underlying sustained fertility declines. Most of the literature on reproductive preferences focuses on stability and variability of adult fertility preferences, and their relationship with behavioural outcomes. Little work has focused on the developmental origins of these preferences, particularly in populations undergoing rapid social and demographic change. This study explores the utility of integrating the ontogeny of fertility preferences into accounts of fertility declines. We analyse data on child and adolescent (age 8–15) reproductive preferences collected from a semi-rural community in the Guatemalan Highlands. We explore (1) the distribution of reproductive preferences across age and gender, (2) relationships between family structure and preferences, (3) the relationship between personal economic and occupational aspirations and reproductive preferences, and (4) the effects of parental investments in education on reproductive preferences. Findings reveal the early development of gender and ethnic differences in reported reproductive preferences, as well as evidence for the differential impact of family background and personal aspirations on the timing of reproductive events and ideal family size.